Relationship Between Husband's Support and the Completeness of Basic Immunization - Christine Manialup; Tut Rayani Aksohini Wijayanti; Reny Retnaningsih (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Immunization is one of the most important health activities necessary for improving children's health, helping prevent various infectious diseases. Despite its crucial role, many children still miss out on receiving complete basic immunization, a concerning public health issue. Among the various factors influencing the successful implementation of immunization programs, the support of family members, particularly husbands, plays a critical role. This study aims to explore the relationship between the support provided by husbands and the basic immunization status of children. A quantitative research design with a cross-sectional approach was employed in this study. The sample consisted of 40 respondents, selected through purposive sampling. The study used the Chi-Square test for data analysis to determine any significant associations between the variables. The results indicate a significant relationship between husband support and the basic immunization status, with a p-value of 0.02. The findings suggest that social support, especially from husbands, is essential in encouraging mothers to ensure their children receive complete immunization. The support not only involves emotional and informational backing but also practical assistance, such as accompanying the mother to health facilities or assisting in scheduling appointments. By involving husbands in the immunization process, mothers may experience less stress and greater encouragement, leading to higher rates of immunization compliance. These results emphasize the importance of engaging family members, particularly husbands, in health initiatives aimed at improving child health outcomes. Public health programs should consider strategies to enhance family involvement, particularly targeting husbands, to achieve better immunization rates and, consequently, improved public health among children